机床调整误差对弧齿锥齿轮大轮齿面形状影响规律的研究 - 李丽霞; 李培军; 刘新状 (Jixie chuandong)
Based on mathematical model, the influential laws of adjustment error of machine tool to the gear tooth surface shape of the spiral bevel gear are analyzed. The points which are affected greatly by the error of the adjustment parameters of machine tool （called the error sensitive points of tooth flank） and the parameters that effect the tooth surface shape of gear greatly among the adjustment parameters of machine tool （called error sensitive adjustment parameters） are found out. The analytic result has theoretical and practice value to compensate the adjustment error of machine tool.